Learning from Young Children: Research in Early Childhood Music - Burton, Suzanne L. (Rowman & Littlefield Publishers, 2011)
In early childhood, the most important period of learning and human development, young children often achieve developmental milestones in a short time. Learning from Young Children: Research in Early Childhood Music presents research on the importance of fostering musical growth during this period. These studies discuss: _